The empirical study on customer satisfaction by using the intergration of manufacturing tools in service industry - Siti Nur Ilika Binti Rusli (2023)
This research has been conducted to study the empirical study on customer satisfaction by using the integration of manufacturing tools in service industry. Manufacturing sector has attracted much attention in recent years. The employment pressure on agriculture has been reduced. It brought in much-needed foreign exchange. It has increased trade and commerce. The manufacturing processes can be determined which raw materials are converted into products. However, in manufacturing there are some of the customer are not satisfied with their service. The customer are expecting that the organization provided the service based on their fulfillment and requirements. Hence the service organization need to define the ways to fulfill the customer requirements. Thus, by using application of service quality (ServQual) and Quality Function Deployment (QFD), it will determine the customer needed and fulfilment in service industry. ServQual is the tools to measure the customer satisfaction. The ServQual consists five dimension which is tangible, assurance, empathy, responsiveness and reliability. In this research, these dimension were applied in the questionnaires for the survey and the questionnaires contain two part which is demographic and ServQual questions. Meanwhile, QFD is a customer-oriented instrument to translate the voice of customers into typical a services. QFD helps to create operational details of the requirements that may be unclear when first expressed. The study will been carried out at Miester Technology Sdn Bhd which is located at Melaka. The results show that the quality plays important role in order to achieve the customer requirements followed by salary and etc. ServQual and QFD ought to be consolidated to get alternate points of view regarding the customer behavior, segmentation and homogeneity; variables to qualify in the customer satisfaction and in the service quality, and distinctive methodologies of how a service industry can gauge the customer satisfaction.